Integrating soil solarization with grafting on resistant rotstocks for management of soil-borne pathogens of eggplant - Ioannou, Nicolas (My University, 2001)
Soil solarization and grafting onto a resistant tomato rootstock ('Brigeor F1'), and the integrated use of both methods were evaluated in four field trials carried out in Cyprus, for management of soil-borne pathogens and pests of eggplant. Soil solarization was highly effective against Verticillium wilt (V. dahliae) but only partially effective against corky root rot (Pyrenochaeta lycopersici) and root-knot nematodes (Meloidogyne spp.); it also controlled adequately most annual weeds. By contrast, grafting provided complete protection from corky root rot and root-knot, but only partial protection from Verticillium wilt. Complete resistance to nematodes, however, occurred only in trials with greenhouse-grown (winter) crops. In open-field (summer) crops, about 50% of the grafted plants sustained slight nematode infection, apparently because of breakdown of resistance at high soil temperatures. Solarization, or grafting gave significant yield increases over that of the untreated check. However, a combination of both was much more effective than either alone. Together, they provided complete protection from all three diseases. Most importantly, they had an additive effect on yield, resulting in a significant increase over that obtained by either method alone. The average yield (kg plant-1) obtained in two greenhouse trials was 9.5 for the control, 16.1 for grafting alone, 14.1 for solarization alone and 20.2 for the combination of the two methods. The integrated use of solarization and grafting appears to be a sustainable alternative to methyl bromide fumigation.
Keywords: Disease resistance; Grafting; Methyl bromide; Nematodiasis; Pest management; Plant disease control; Plant growth; plant pathogen interaction; Plant yield; Soil solarization